2017
DOI: 10.1111/his.13156
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive screening for MED12 mutations in gynaecological mesenchymal tumours identified morphologically distinctive mixed epithelial and stromal tumours

Abstract: These MED12-mutated adenosarcoma-like tumours might represent a distinct entity that requires more studies for its identification. MED12 exon 2 mutations seemed to have no significant role in other uncommon gynaecological mesenchymal tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Studies have shown that MED12 mutations in fibroadenomas are associated with dysregulation of estrogen signaling ( 27 ). This suggests that MED12 mutations may play a crucial oncogenic role in estrogen-related ESS ( 28 ). The study reveals that mutations in exon 2 of MED12 have been identified in ESS carrying the JAZF1-SUZ12 or JAZF1-PHF1 fusion genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that MED12 mutations in fibroadenomas are associated with dysregulation of estrogen signaling ( 27 ). This suggests that MED12 mutations may play a crucial oncogenic role in estrogen-related ESS ( 28 ). The study reveals that mutations in exon 2 of MED12 have been identified in ESS carrying the JAZF1-SUZ12 or JAZF1-PHF1 fusion genes.…”
Section: Discussionmentioning
confidence: 99%
“…The study reveals that mutations in exon 2 of MED12 have been identified in ESS carrying the JAZF1-SUZ12 or JAZF1-PHF1 fusion genes. These mutations may confer additional oncogenic advantages ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the MED12 gene is closely related to uterine leiomyoma [ 17 ]. The 70% of uterine leiomyomas have point mutations in the MED12 gene, and all relevant point mutations are concentrated in exon 2 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the MED12 gene is closely related to uterine leiomyoma [ 17 ]. The 70% of uterine leiomyomas have point mutations in the MED12 gene, and all relevant point mutations are concentrated in exon 2 [ 17 ]. MED12 mutations alter the functioning of the MED12 protein, thus disrupting normal cell signalling and repair regulation of cell growth and other functions, resulting in uncontrolled cell growth and tumorigenesis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular background of adenomyomas is not well known and most studies looking into their genetic and molecular features have focused on the rare subtype of atypical polypoid adenomyoma (APA) (Takahashi et al , 2014; Nemejcova et al , 2015; Yuan et al , 2017). Here, we have analysed the contribution of uterine leiomyoma driver events— MED12 mutations, HMGA2 overexpression, and FH inactivation—in 21 adenomyoma samples from 21 patients.…”
Section: Introductionmentioning
confidence: 99%